Eavesdropping Technology Part II - Poh, Wei Quan (2016)
Eavesdropping technology has long been of particular interest to security organizations and governments. The improvement of this technology is important for the enhancement of surveillance especially in the face of rising global threats. Its use in commercial applications has also been increasingly explored, in conjunction with the development of automatic speech recognition applications. In this final year project, the effectiveness of beamforming algorithms is explored using automatic speech recognition programs.